Pengaruh Permainan Kecil dalam Pemanasan Terhadap Motivasi Siswa - Wulandari, Meylani Ayu; Hidayat, Abdul Salam; Nugroho, Setio (Universitas Hamzanwadi, 2022)
The purpose of this study was to determine the effect of small games in warming up on student motivation in physical education learning. This study uses a quantitative approach. The research method used in this study is an experimental research method. This type of research is Pre-Experimental Design. While the form of research using the form of One - Group Pretest-Posttest Design. The implementation of this research was carried out in three stages, namely pretest, treatment, and posttest. This research was conducted at SMA Negeri 1 Telukjambe Barat. The population used is all students of class XI IPA 2, totaling 197 students. The sample in this study is cluster random sampling, namely class XI IPA 2, totaling 32 students. The independent variable is a small game in warming up and the variable is motivation to learn. The research instrument used a learning motivation questionnaire and data collection techniques with a Likert scale. Data analysis was carried out by testing validity, reliability, normality test, homogeneity test, and hypothesis testing. the results based on the calculation of the average pretest 84.00 and the average posttest results of 87.96. Result of t count -6.078 > t table 2.040. The magnitude of the effect is 4.51%. Thus it can be said that there is a significant effect of small games in warming up on students' motivation in physical education learning.